2020
DOI: 10.1002/micr.30580
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of denervated muscle atrophy with accelerated nerve‐regeneration by babysitter procedure in rat facial nerve paralysis model

Abstract: Purpose The “babysitter” procedure is a reconstruction technique for facial nerve complete paralysis and uses the movement source from the healthy facial nerve with a cross‐nerve graft. First, an end‐to‐side neurorrhaphy is performed between the affected facial nerve trunk and hypoglossal nerve for continuously delivering stimuli to the mimetic muscles for preventing the atrophy of mimetic muscles. Despite favorable clinical results, histological and physiological mechanisms remain unknown. This study attempte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…A babysitter procedure is the process of coapting an additional donor nerve to a nerve graft, distal to the primary neurorrhaphy 40 . This procedure has been described in situations, such as in parotidectomies, where a segment of the facial nerve requires excision due to tumor involvement [41][42][43][44] . In this scenario, a nerve graft is typically used to bridge the nerve gap.…”
Section: 'Babysitter' Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…A babysitter procedure is the process of coapting an additional donor nerve to a nerve graft, distal to the primary neurorrhaphy 40 . This procedure has been described in situations, such as in parotidectomies, where a segment of the facial nerve requires excision due to tumor involvement [41][42][43][44] . In this scenario, a nerve graft is typically used to bridge the nerve gap.…”
Section: 'Babysitter' Proceduresmentioning
confidence: 99%
“…40 This procedure has been described in situations, such as in parotidectomies, where a segment of the facial nerve requires excision due to tumor involvement. [41][42][43][44] In this scenario, a nerve graft is typically used to bridge the nerve gap. To minimize irreversible end-plate degeneration, an alternative donor motor nerve can be used such as hypoglossal nerve.…”
Section: "Babysitter" Proceduresmentioning
confidence: 99%
“…For years, researchers have never stopped looking for effective treatments to promote facial nerve regeneration [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that nerve injuries induce a variety of molecular responses that may be involved in the regeneration of injured neurons [ 11 , 13 16 ]. In the neurons, the efficacy and the specificity of neurotrophic factors to support regeneration depend on the presence of their respective receptors and their number.…”
Section: Introductionmentioning
confidence: 99%